Remote Fieldwork With African Migrant Women During COVID-19 Pandemic in London: A Reflection - Madziva, Cathrine; Chinouya, Martha Judith (Frontiers in Sociology, 2022)
As coronavirus disease 2019 (COVID-19) pandemic unraveled, state-led preventative restrictions created a “new” normal through remote home-working. A long-planned follow-up qualitative research study on risk perceptions and experiences regarding Clay Ingestion among black African women during pregnancy, in London, was disrupted as England went into lockdown. Against this backdrop, we shifted to remote data collection which raised pertinent concerns around access to technology and participant digital skills. We share our experiences of navigating through remote fieldwork during the pandemic with black African mothers with caring responsibilities as well as the extra burden of homeschooling, the challenges we encountered and how we mitigate these and the lessons learnt. Thus, drawing from our remote qualitative research experiences, we refer to notable examples of challenges, mitigating strategies applied and potential lessons to inform future practice.